Práticas de letramento na formação de leitores/as infantis como sujeitos críticos: autoetnografia de uma professora no ensino fundamental - Borges, Sandra Helena (2020)
This research, located in the scope of Applied Linguistics, is an evocative autoethnography (ELLIS, 1991, 2004). In it, I narrate literacy practices (STREET, 2007, 2012, 2013) in the training of young readers that I planned and executed, in the year 2018, in a class of 2nd grade of Elementary School, at a municipal public school in Uberlândia-MG, in which I am a teacher of the discipline Literature and other languages. My objective is to show how and to what extent these literacy practices, conceived in the perspective of the Ricoeurian hermeneutics, can lead to the formation of young readers as critical subjects. The path of evocative autoethnographic research that I followed, in this thesis, assumes that a good history of oneself (ELLIS, 2004) is theoretical, because when telling it, the person uses analytical techniques to interpret his/her world. To compose the empirical materials with which I theorize or tell this story, I use my memory, the reading diaries of twenty-four children, seven to eight years old, who were my students, interviews that I did with them focused in these diaries, and my ethnographic research diary. I concluded this research by answering the question that arose from it, namely: how and to what extent literacy practices that I plan and execute, conceived in the perspective of ricoeurian hermeneutics, can lead to the formation of young readers as critical subjects? Well, combining, readings, analyzes and reflections; and trusting in the capacities of these subjects of power and action. Analyzing imposes the indirect and fragmentary way of each and every return to oneself, and reflecting links understanding of the text and understanding of oneself (RICOEUR, 2014). This answer is not a truth, but only a becoming (DELEUZE; PARNET, 1998). The narration of literacy practices in the training of young readers that I planned and executed, in 2018, provided an expansion of my understanding of these practices, of myself and, consequently, of myself in the world and, still, made it clear how I am molding and implementing a tool, attitude and philosophy of critical literacy (SOUZA, 2011a, 2011b; TAGATA, 2017, 2018), through the critical hermeneutics by Ricoeur (1986, 1990, 1997,1988, 2000, 2014).